Organizational theory in higher education. - Manning, Kathleen (Core concepts in higher education., 2013)
Organizational Theory in Higher Education offers a fresh take on the models and lenses through which higher education can be viewed by presenting a full range of organizational theories, from traditional to current. By alternating theory and practice chapters, noted scholar Kathleen Manning vividly illustrates the operations of higher education and its administration. Manning's rich and interdisciplinary treatment enables leaders to gain a full understanding of the perspectives that operate on a college campus and ways to adopt effective practice in the context of?new and continui.